The effect of fine particulate matter exposure on allergic rhinitis of adolescents aged 10–13 years: A cross-sectional study from Chongqing, China - Qiu, Chunlan; Feng, Wei; An, Xizhou; Liu, Fangchao; Liang, Fengchao; Tang, Xian; Zhang, Ping; Liang, Xiaohua (Frontiers in Public Health, 2022)
Background Allergic rhinitis (AR) has become a tremendous disease burden worldwide. Only a few studies have explored the effects of environmental exposure on the prevalence of AR in children in China. Methods In the present study, we investigated the associations of environmental exposure (including fine particulate matter (PM2.5), air humidity, temperature, and passive smoking) with AR in adolescents aged 10–13 years in Chongqing. Data from 4,146 participants in urban and rural areas between March 2019 and May 2019 were collected. Results The overall prevalence of AR was 17.50% in adolescents. After adjusting for other covariates, AR was positively correlated with the annual mean PM2.5 concentration, monthly mean PM2.5 concentration and air temperature, and negatively related to air humidity. Furthermore, the annual mean PM2.5 was positively associated with the risk of AR after adjusting for air temperature and humidity. Passive smoking (PS) was marginally associated with a high risk of AR. Conclusion High PM2.5 exposure, high air temperature, and low air humidity were associated with a high risk of AR in adolescents. Our findings have potential implications for public health strategies and interventions aimed at reducing the burden of AR in adolescents.